Identification of TRPV4 as a novel target in invasiveness of colorectal cancer - Peng Zhang (BMC, 2021)
Abstract Background Emerging evidence has indicated the critical role of TRPV4 in diverse human cancers. However, the underlying molecular mechanism of TRPV4 in colon cancer invasiveness is still unknown. Methods Immunohistochemistry staining was used to analyze the expression of TRPV4 and ZEB1 in clinical tissues; Wound healing and transwell assays were applied to determine the cell invasiveness; Western blot was used to explore the relation between TRPV4 and ZEB1. Results Colon cancer cells were transfected with siRNA against TRPV4 or HC067047 (a selective TRPV4 antagonist), TRPV4 full-length plasmid or siRNA against ZEB1, or both, in order to measure cell migration and invasion. And we found that TRPV4 silencing or inhibition exhibited an inhibitory role in colon cancer cell migration and invasion, coupled with compromised EMT process, and suppressed AKT activity. TRPV4 stimulated expression of ZEB1 and consequently contributed to EMT process and invasiveness. It was also revealed that overexpression of TRPV4 and ZEB1 in clinical patients with local metastasis, and positive correlation between TRPV4 and ZEB1. Conclusions Our results uncovered the role of TRPV4 in tumor metastasis and highlighted the potential mechanism of TRPV4-ZEB1 axis in indicating EMT.